Pengaruh Aktivitas Menggambar Batik Magic Color Terhadap Kreativitas Anak di Taman Kanak-kanak Pertiwi 1 Kantor Gubernur Padang - Julia Yonika; Farida Mayar; Elise Muryanti; Tisna Syafnita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article is based on research results that are motivated by the low creativity of early childhood and the lack of variety of learning activities that can provide optimal stimulation. This condition causes children's creativity not to develop optimally. To overcome this problem, the Batik Magic Color drawing activity is implemented as an interesting, fun art activity, and is able to provide opportunities for children to explore, imagine, and express their ideas creatively. This study aims to determine the effect of the Batik Magic Color drawing activity on the creativity of group B children at Pertiwi 1 Kindergarten, Padang Governor's Office. The method used is a quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design), which involves two groups, namely the experimental group that was given treatment in the form of Batik Magic Color drawing activities and the control group that followed conventional learning. The research sample consisted of class B3 as the experimental class with a total of 16 children and class B5 as the control class with a total of 16 children selected using a purposive sampling technique. Data collection techniques used observation, assessment of work results, and documentation. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis testing using the Independent Sample t-test. The results of the study showed that the average creativity score of children in the experimental class increased from 8.81 in the pre-test to 21.50 in the post-test. The results of the hypothesis test obtained a Sig. (2-tailed) value of 0.001 < 0.05, so it can be concluded that there is a significant influence of the Batik Magic Color drawing activity on the creativity of group B children at Pertiwi 1 Kindergarten, Padang Governor's Office.